Analisis Hubungan Tingkat Pengetahuan dengan Kejadian Acute Mountain (AMS) Sickness pada Mahasiswa Pecinta Alam - Sri Wahyuni; Siti Rahmani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the climbers' understanding of AMS and the incidence of AMS that has been experienced while climbing. This research method is quantitative research with a cross-sectional study approach. The results of this study indicate the level of knowledge of 128 respondents (85.3%) in the excellent category. The incidence of AMS in most climbers experienced mild AMS among as many as 86 respondents (57.30%). In conclusion, there is no relationship between knowledge and AMS incidence in mountaineering students in Makassar City. Keywords: Acute Mountain Sickness (AMS), Climber, Knowledge